Islam di Era Digital: Analisis Tren dan Tantangan di Masa Disrupsi - Khairil Anwar; Zulkifli (Research Institute and Community Engagement of UIN MADURA, 2026)
This study examines the trends in the development of Islam in the era of digital disruption, where technological advancements have influenced various aspects of Muslim religious life. With the widespread use of the internet, social media, and other digital platforms, religious practices, da'wah, and Islamic education have undergone significant transformation. Through a qualitative approach that examines various relevant literature sources to study the phenomenon of digitalization in Islamic religious life, this research analyzes both the positive and negative impacts of digitalization on Islamic preaching, religious education, and the formation of a global Muslim community. The findings reveal that digitalization offers numerous opportunities, such as easier access to religious information, the global expansion of Islamic da'wah, and the emergence of online Islamic education platforms that facilitate distance learning. However, the era of digital disruption also presents major challenges, including the rampant spread of unverified information, the risk of religious privatization that reduces social engagement, and the potential for radicalization through digital media. This study recommends the need for a wise adaptation by preachers, educators, and religious institutions to maximize the benefits of digital technology in strengthening Islamic teachings, while maintaining the authenticity and validity of disseminated information by instilling deep-rooted values of wasathiyah (Islamic moderation). In this way, Islam can remain relevant and continue to grow dynamically amidst the challenges of the digital age.